Percepção de profissionais da ESF sobre a inserção da residência de Medicina de Família e Comunidade nas suas equipes - Freitas, Jandira Arlete Cunegundes de (2019)
The central theme of this study is the insertion of the Family and Community Medicine residency in Basic Health Units, analyzed from the perspective of team professionals of the Family Health Strategy. The objectives are to describe and analyze this insertion in their practice scenario, based on the vision of the workers of these teams, as well as the contribution of this interprofessional team on the training of residents. The research model was descriptive, with a qualitative approach. The participants were 27 professionals who are part of five teams enrolled in four Basic Health Units of the city of Mossoró-RN (three nurses, one nursing technician, 21 community health agents, one dental technician and one dental assistant The interviews were carried out through the technique of the focal group, with audio recording, later transcription and content analysis proposed by Bardin, through the thematic analysis, the following categories emerged: residence and their presence in the team, residence and the work process, residence and community and residence and management.The research allowed an analysis of several aspects related to the insertion and performance of the residence in the referred units, highlighting potentialities and weaknesses in this process.